Analisis faktor-faktor yang berhubungan dengan kualitas hidup penderita hipertensi - Nurul Atika; Samino Samino; Nurhalina Sari (Holistik Jurnal Kesehatan, 2022)
Background: The prevalence of hypertension in Lampung Province was 15.10 percent and the majority affects the pre-elderly and the elderly. The prevalence of hypertension in Pesisir Barat was 12.22 percent and at Puskesmas Krui was 21.19 percent. Treatment and care services for hypertension aim to improve the quality of life of patients. The purpose of this study was to analyze factors related to the quality of life of patients with hypertension in the posyandu for the elderly in the working area of the Puskesmas Krui Pesisir Barat.Purpose: To determine the factors related to the quality of life of hypertensive patients in the Elderly Posyandu in the working area of the Krui Pesisir Barat Health Center.Method: Quantitative with a cross-sectional design, a population of 998 people and a sample of 514 people with purposive sampling, then analyzed by chi square and logistic regression.Results: Showed that there was a relationship between adherence to antihypertensive medication (p value <0.001 OR=2.0), physical activity (p-value <0.001 OR=5.5), comorbid disease (p-value <0.001 OR=4.2), stress level (p value <0.001 OR=2.6) with quality of life. The variable of physical activity became the variable with the most dominant influence on the quality of life with an OR of 4.4, followed by a comorbid variable with an OR of 2.9. Conclusion: physical activity is the most influential variable with the quality of life of hypertensive patients at the Elderly Posyandu with an OR of 4,4.Suggestion: The management of the Pesisir Barat District Health Office to facilitate the elderly with hypertension in sports facilities such as green open spaces for the elderly for elderly gymnastics activities, conducting healthy walking competitions for the elderly and complete equipment such as sound systems for the continuity of the activities of the elderly posyandu, especially to improve the quality of life.Conclusion: There is a relationship between the quality of life of patients with hypertension at the Posyandu for the elderly at the Krui Pesisisr Barat Public Health Center.Keywords: Integrated Service for the Elderly; Hypertension; Quality of Life.Pendahuluan: Prevalensi hipertensi di Provinsi Lampung 15,10 persen dan mayoritas diderita pra lansia dan lansia. Prevalensi hipertensi di Pesisir Barat sebesar 12,22 persen dan di Puskesmas Krui sebesar 21,19 persen. Pelayanan pengobatan dan perawatan hipertensi bertujuan meningkatkan kualitas hidup penderita. Tujuan dari penelitian ini adalah menganalisis factor yang berhubungan dengan kualitas hidup penderita hipertensi di posyandu lansia wilayah kerja Puskesmas Krui Pesisir Barat.Tujuan: Untuk menganalisa faktor-faktor yang berhubungan dengan kualitas hidup penderita hipertensi di Posyandu Lansia Wilayah Kerja Puskesmas Krui Pesisir Barat.Metode: Jenis penelitian kuantatif dengan rancangan potong lintang, populasi 998 orang dan sampel 514 orang dengan purposive sampling, lalu dianalisis dengan chi square dan regresi logistik.Hasil: Hasil penelitian mendapatkan ada hubungan kepatuhan minum obat anti hipertensi (p value <0,001 OR=2,0), aktivitas fisik (p value <0,001 OR=5,5), adanya penyakit komorbid (p value <0,001 OR=4,2), tingkat stress (p value <0,001 OR=2,6) dengan kualitas hidup. Variabel  aktivitas fisik menjadi variabel yang paling dominan pengaruhnya terhadap kualitas hidup dengan OR 4,4 disusul oleh variable komorbid dengan OR 2,9. Kesimpulan: aktivitas fisik merupakan variable yang paling berpengaruh dengan kualitas hidup penderita hipertensi di Posyandu Lansia dengan OR 4,4.Saran: Dinas Kesehatan Kabupaten Pesisir Barat agar memfasilitasi lansia penderita hipertensi akan fasilitas olahraga seperti ruang terbuka hijau untuk lansia beraktivitas senam lansia, melakukan lomba jalan sehat bagi lansia serta peralatan kelengkapan alat seperti sound sistem untuk keberlangsungan kegiatan aktivitas posyandu lansia khususnya untuk meningkatkan kualitas hidup.Simpulan: Terdapat hubungan Kualitas hidup penderita hipertensi di posyandu lansia Puskesmas Krui Pesisisr Barat.